2020
DOI: 10.3390/cli8040050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change Impacts on Sea Surface Temperatures and Sea Level Rise—The Arabian Gulf

Abstract: The Arabian Gulf is one of the regions in the world experiencing major changes due to increased economic growth rates and development practices. As a shallow water body within a hot desert, the Gulf is exposed to obvious warming in the sea surface temperatures (SST). Remotely sensed SST data were utilized to estimate decadal change in SST with a focus on coral reef locations. There is a positive trend in monthly time series SSTs, with a maximum value of about 0.7 °C/decade for the western side of the Gulf. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…Compared to the global and Red Sea SST warming rates of 0.07 and 0.17 (max 0.45) • C/decade (Lough, 2012;Chaidez et al, 2017), respectively, the Gulf 's warming rate was found here to be 0.41 (±0.14) • C/decade. Hereher (2020) determined the Gulf 's warming trend to be 0.7 • C/decade using observations from Moderate Resolution Imaging Spectroradiometer (MODIS) images for the period of 2003 to 2018; this is similar to the observations obtained here for the same time period (0.67 • C/decade). In addition, the results obtained here showed that the Gulf 's spatial SST warming trend displayed a latitudinal gradient of 0.22 to 0.59 • C/decade, with steeper trends from south to north.…”
Section: Gulf's Warming Ratesupporting
confidence: 80%
“…Compared to the global and Red Sea SST warming rates of 0.07 and 0.17 (max 0.45) • C/decade (Lough, 2012;Chaidez et al, 2017), respectively, the Gulf 's warming rate was found here to be 0.41 (±0.14) • C/decade. Hereher (2020) determined the Gulf 's warming trend to be 0.7 • C/decade using observations from Moderate Resolution Imaging Spectroradiometer (MODIS) images for the period of 2003 to 2018; this is similar to the observations obtained here for the same time period (0.67 • C/decade). In addition, the results obtained here showed that the Gulf 's spatial SST warming trend displayed a latitudinal gradient of 0.22 to 0.59 • C/decade, with steeper trends from south to north.…”
Section: Gulf's Warming Ratesupporting
confidence: 80%
“…(2007) . Global average sea-level is rising at an average rate of 3.36 ± 0.4 mm yr −1 and PG sea-level rise more or less is the same ( Church and White 2006 ; Hereher 2020 ). The combined impact of sea-level rise and increasing temperatures has negatively impacted the sensitive ecosystems of the Gulf i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The combined impact of sea-level rise and increasing temperatures has negatively impacted the sensitive ecosystems of the Gulf i.e. the coral reefs, with coral bleaching and death being reported (Kabiri et al, 2012;Hereher 2020;Riegl 2003). Long lasting high SST in the PG is the cause of coral bleaching incidents in 1996in , 1998in , 2002in , 2007in , 2017).…”
Section: The Changing Environmentmentioning
confidence: 99%
“…For the MODIS data, thermal channels 31 (10.780 to 11.280 µm) and 32 (11.770 to 12.270 µm) are particularly suited to estimate the surface temperature [40]. The MODIS sea surface temperature data have been widely validated for open waters and therefore are widely accepted as accurate [37,[41][42][43][44][45].…”
Section: Sst Datamentioning
confidence: 99%